2021
DOI: 10.1038/s41598-021-03334-4
|View full text |Cite
|
Sign up to set email alerts
|

The Edible Plant Microbiome represents a diverse genetic reservoir with functional potential in the human host

Abstract: Plant microbiomes have been extensively studied for their agricultural relevance on growth promotion and pathogenesis, but little is known about their role as part of the diet when fresh fruits and vegetables are consumed raw. Most studies describing these communities are based on 16S rRNA gene amplicon surveys, limiting our understanding of the taxonomic resolution at the species level and functional capabilities. In this study, we characterized microbes colonizing tomatoes, spinach, brined olives, and dried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 85 publications
0
16
1
Order By: Relevance
“…In ancient times, fermentation was a common way for food preservation and processing. At present, fermented food plays an important role in human diets due to its special taste and unique aroma ( Marco et al, 2021 ; Soto-Giron et al, 2021 ). In addition, the health-related properties of fermented food significantly promote their consumption around the world ( Castellone et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In ancient times, fermentation was a common way for food preservation and processing. At present, fermented food plays an important role in human diets due to its special taste and unique aroma ( Marco et al, 2021 ; Soto-Giron et al, 2021 ). In addition, the health-related properties of fermented food significantly promote their consumption around the world ( Castellone et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“… 42 Exposure to diverse bacteria via fruit and vegetable consumption could have a significant impact on the genetic diversity of the gut microbiota, in particular during childhood. Interestingly, Soto-Giron et al 16 showed high genetic diversity and specific functions of plant-associated strains of Pseudomonas and Lactobacillus , and specific functions associated with probiotic-linked mechanisms. Limited exposure to diverse microbiota may influence immune system development.…”
Section: Resultsmentioning
confidence: 99%
“…Fruits and vegetables do not only contain nutrients and bioactive plant secondary metabolites that are known to influence the gut microbial diversity and composition, 13 but also a high diversity of microorganisms. 14 , 15 Therefore, it was hypothesized that fruits and vegetables serve as the main direct sources of environmental microbiota 14 , 16 and may modulate the composition and functionality of our gut microbiomes. 17 However, there has been no study to date to investigate the potential transfer of the natural fruit and vegetable microbiota to the human gut.…”
Section: Introductionmentioning
confidence: 99%
“…Fruits and vegetables harbor an immensely diverse microbiome essential for the health and survival of the plant. [10][11][12] This untapped source of microbial diversity has facilitated the development of a novel, safe, Defined Microbial Assemblage ™ (DMA TM ) medical food product, SBD111, for the dietary management of the metabolic processes associated with osteopenia and osteoporosis. SBD111 is composed of four strains of microorganisms isolated from different food sources: Lactobacillus brevis SBS4254, Lactobacillus plantarum SBS4260, Leuconostoc mesenteroides SBS4255, and Pichia kudriavzevii SBS4263, as well as oligofructose and dried blueberry powder.…”
Section: Introductionmentioning
confidence: 99%